Audio-visual aids and foreign language learning: a case study of french language in Nigeria (2013)
In the last century, trends in the teaching of foreign language had resulted into the emergence of a number of methods and approaches to the teaching and learning of foreign language across the world. Due to globalization and urbanization and the tendency in man to reduce the world into a global village through breaking the communication barriers via foreign language learning, attempt has been made to revolutionize the teaching and learning of foreign languages using audio-visual aids. Suffice,to say that audio-visual aids combine both the motivational and learning features. However, it is not an end in itself but a means to an end. The full potentials and benefits derivable from using audio visual aids in foreign language class have not been fully exploited. This may be considered as one of the factors underlying high rate of drop-out or attrition in the foreign language class. This paper therefore highlights the significance of using audio visual aids in the teaching and learning of foreign languages.